Status Trofik Perairan Danau Laguna, Kota Ternate Selatan, Maluku Utara - Ardan Samman; Mesrawaty Sabar; M. Abjan Fabanjo; Rina Rina; Rugaya Serosero; Salim Abubakar; Sunarti Sunarti (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2023)
Water quality and trophic status of waters play an important role in aquaculture activities because they will affect the growth process of cultivated fish, if the water quality and trophic status are low then they can support aquaculture activities in the waters of Laguna Lake, South Ternate City. The purpose of this study was to determine the water quality and trophic status in the waters of Laguna Lake in supporting and supporting freshwater aquaculture activities. The research method used in this research is descriptive qualitative, the results of air analysis are described based on Class and Water Quality Standards, while the trophic status is estimated based on Carlson, 1977. The results of the analysis show that the water quality in Laguna Lake is still in accordance with Class II Quality Standards. PP No. 22 of 2021, while the trophic level status in Laguna Lake is also classified in the oligotrophic category, namely TSI <40, TSI in Laguna Lake waters ranges from 20.69-23.28. Based on the results of the analysis of water quality and trophic status, it was found that the waters of Laguna Lake are still good and can support freshwater fish farming activities